2014
DOI: 10.3109/10717544.2014.923064
|View full text |Cite
|
Sign up to set email alerts
|

Brain targeting by intranasal drug delivery (INDD): a combined effect of trans-neural and para-neuronal pathway

Abstract: The effectiveness of intranasal drug delivery for brain targeting has emerged as a hope of remedy for various CNS disorders. The nose to brain absorption of therapeutic molecules claims two effective pathways, which include trans-neuronal for immediate action and para-neuronal for delayed action. To evaluate the contribution of both the pathways in absorption of therapeutic molecules and nanocarriers, lidocaine, a nerve-blocking agent, was used to impair the action potential of olfactory nerve. An anti-Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This finding suggests that a large portion of the instilled dose is absorbed through the nasal cavity and directly delivered to the brain. In correspondence, many studies showed that absorption of substances through intranasal cavity provides them a direct delivery to the brain through both the olfactory and trigeminal nerves [16]. In agreement, other research groups reported a brain-targeted distribution of manganese [25] and silver [26] following intranasal instillation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This finding suggests that a large portion of the instilled dose is absorbed through the nasal cavity and directly delivered to the brain. In correspondence, many studies showed that absorption of substances through intranasal cavity provides them a direct delivery to the brain through both the olfactory and trigeminal nerves [16]. In agreement, other research groups reported a brain-targeted distribution of manganese [25] and silver [26] following intranasal instillation.…”
Section: Discussionmentioning
confidence: 62%
“…More importantly, it has been found that a large part of these substances, absorbed nasally, could be delivered directly to the brain within minutes along both the olfactory and trigeminal nerves [16]. In animals, several metals have been shown to pass via the olfactory receptor neurons from the nasal lumen through the cribriform plate to the olfactory bulb.…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal drug delivery is a novel and safe way to administer medications through the nasal mucosa (Farzampour et al, 2016 ). This route of drug administration shunts the BBB, is non-invasive and encompasses two separate pathways including trans-neuronal or immediate and para-neuronal or delayed (Mustafa et al, 2016 ). It has been shown that nicotine nasal spray improves continuous attention, working memory, and executing processing (Smith et al, 2002 ; Myers et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, within the last years, propagation of AD pathology via a neuronal cell-to-cell transfer has been suggested by cell culture and animal experiments [ 69 , 70 ]. In transnasal delivery, however, trans-neuronal and para-neuronal pathways seem to contribute depending on the administered drug formulation [ 71 ]. As we did not investigate the spreading of the exogenously applied peptides within the brain further, we cannot speculate yet on the route taken.…”
Section: Discussionmentioning
confidence: 99%